Malware detection based on visualization of recombined API instruction sequence - Hongyu Yang; Yupei Zhang; Liang Zhang; Xiang Cheng (Connection Science)
This paper introduces a malware detection method based on the reorganisation of API instruction sequence and image representation in an effort to address the challenges posed by current methods of malware detection in terms of feature extraction and detection accuracy. In the first step, APIs of the same type are grouped into an API block. Each API block is reorganised according to the ﬁrst invocation order of each type of API. As a measure of the API's devotion to the software sample, the number of API block entries is recorded. Second, the API codes, API devotions, and API sequential indexes are extracted based on the reorganised API instruction sequence to generate the feature image. The feature image is then fed into the self-built lightweight malware feature image convolution neural network. The experimental results indicate that the detection accuracy of this method is 98.66% and that it has high performance indicators and detection speed for malware detection.